Remote Monitoring In Clinical Trial – A Guide for Healthcare Professionals - Pachiappan, Sudhakar; Gnanasambandam, Anjali; Preethi Samundi, Selva; Parameshwaran, Selva Prasanthi; Hassan Ali, Asma Fathumuthu; Saravanan, Poorana Pushkalai (Asian Journal of Pharmaceutical Research and Development, 2023)
Remote monitoring is a key step in clinical research that produces reliable, high-quality, and scientifically sound data from clinical studies. According to ICH-GCP, the sponsor has the responsibility for preserving the monitoring of data for the continuing trials. Due to the development of remote monitoring, the monitoring of the trials has become fairly simple for the CRA (a person assigned by the sponsor to monitor the ongoing trials). The primary benefit of remote monitoring is that it speeds up the on-time completion of work by reducing the time required for final trial reports output. It significantly lowers the sponsor's travel costs. Reducing the time between site monitoring enhances the accuracy and timeliness of study data and increases the safety of human subjects participating in a clinical trial. By using the secure off-site electronic health records access is currently utilized for clinical care, and also used to validate the source documentation. This article provides an overview of the offsite monitoring processes involved and standards adopted in remote monitoring.